Using XML-based Metadata for Generating Dynamic Courseware - Osman, Mashanum; Razali, Sazalinsyah (2005)
The objective of this paper is to explore the mechanism between the learner and learning material in generating dynamic courseware in e-learning environment, The dynamic e-learning develop flexible and dynamic course content according to the suitability level of learner, This dynamic e-learning will be using XML-based metadata in particular. XML based metadata allows any part of a course to be modularized, saves and reused as a learning object. Each learning object is described in the object repository. Learning objects are stored in central object repository and are easily locatable on an object-by-object basis. To achieve learner adaptability, learners are allowed to specify queries that will dynamically construct courses.